Smart city governance and interoperability: enhancing human security in Yogyakarta and Makassar, Indonesia - Hardi, Rudi; Nurmandi, Achmad; Purwaningsih, Titin; Manaf, Halimah Abdul (Frontiers in Political Science, 2025)
IntroductionThe global expansion of smart cities has reshaped urban governance; however, their heavy reliance on technological innovation often undermines human security, leading to fragmented, unsustainable, and exclusionary systems that fail to meet the needs of vulnerable populations. This study examines the impact of interoperability on smart city governance (SCG) and its role in enhancing human security in Yogyakarta and Makassar, Indonesia.MethodsThe research explores how interoperability is developed through design processes, government alignment, policy fit, user engagement, change management, governance structure, and service consumption. Data were collected from 315 respondents across 47 government agencies and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).ResultsThe findings indicate that interoperability significantly strengthens SCG and enhances human security. Cross-sector collaboration emerged as a key driver of innovation. Despite challenges such as regulatory resistance and data fragmentation, alignment with the national digital strategy, SPBE policy, and Indonesia’s One Data initiative facilitates system integration.Discussion and conclusionThis study shifts the focus of smart city development from technological advancement to addressing urban vulnerabilities. It provides a blueprint for cities like Yogyakarta and Makassar to integrate local policy frameworks with global standards, thereby promoting responsive and equitable urban governance.